The New Testament library : 1 & 2 Timothy and Titus : a commentary - Collins, Raymond F., 1935- (Louisville : Westminster John Knox Press, 2002)
The Pastoral Epistles present difficult questions for the modern interpreter, including such matters as their authorship, literary characteristics, and social orientations. Raymond Collins carefully leads the reader through the texts of these three documents, attending to the flow of the Pastor's thought and locating it within the Jewish and Hellenistic culture of his day. The New Testament Library offers authoritative commentary on every book and major aspect of the New Testament, as well as classic volumes of scholarship. The commentaries in this series provide fresh translations based on the best available ancient manuscripts, offer critical portrayals of the historical world in which the books were created, pay careful attention to their literary design, and present a theologically perceptive exposition of the text.
Introduction to the Pastoral Epistles -- 1 Timothy -- 2 Timothy -- Titus.
Includes bibliographical references (pages xviii-xxiv) and indexes.
Keywords: Bible. -- Commentaries; Timotheus (bijbelboeken); Titus (bijbelboek); Bible -- N.T -- Timothy, 1st -- Commentaries; Bible -- N.T -- Timothy, 2nd -- Commentaries; Bible -- N.T -- Titus -- Commentaries